Hypertension in Acromegaly in Relationship to Biochemical Control and Mortality: Global ACROSTUDY Outcomes - Vila, Greisa; Luger, Anton; van der Lely, Aart Jan; Neggers, Sebastian J. C. M. M.; Webb, Susan M.; Biller, Beverly M. K.; Valluri, Srinivas; Hey-Hadavi, Judith (Frontiers in Endocrinology, 2020)
Context: Hypertension is a major cardiovascular risk factor related to increased mortality in acromegaly. Surgical cure of acromegaly is associated with improvement in blood pressure levels, however little is known about the effect of pegvisomant (PEGV) treatment in patients with hypertension. This analysis evaluates outcomes in patients with hypertension and acromegaly included in ACROSTUDY. Methods: ACROSTUDY is a global non-interventional surveillance study of long-term treatment with PEGV, monitoring its safety and efficacy. The cohort was retrospectively divided in two subgroups: patients with and without hypertension. Stepwise logistic regression and Kaplan-Meyer analyses were performed for testing predictors of mortality. Results: The total cohort included 2090 patients with acromegaly treated with PEGV who were followed for a median of 6.8 years (range up to 12.1 yrs). At ACROSTUDY start, there were 1344 patients with hypertension (52.3% males). This subgroup was older, had a higher BMI, and higher prevalence of diabetes, hyperlipidemia, and cardiovascular disease (CVD) when compared to patients without hypertension. During ACROSTUDY, 68 deaths were reported in the hypertension cohort, vs 10 in the cohort without hypertension. Both CVD (p<0.0001) and anterior pituitary deficiencies (p=0.0105) at study entry independently predicted mortality in patients with acromegaly and hypertension; Kaplan-Meier analysis confirmed that CVD significantly impairs survival. Conclusions: Hypertension is common in patients with acromegaly and significantly increases mortality, especially when there is concomitant CVD. These data suggest that treatment goals should extend beyond IGF-I normalization, and include optimisation of substitution of pituitary deficiencies and scrutinous screening and treatment of CVD.